1892 N.J. Laws 353 - (:unkn) unknown (My University, 1892)
Ch. 217, 1-2: That if any person shall be apprehended in any city of this state, having concealed upon his or her person any offensive weapon, then he or she shall be deemed and adjudged to be a disorderly person; provided, that this act shall not apply to sheriffs, under sheriffs, deputy sheriffs, constables, policemen or other peace officers, nor to any person having a written permit from the police authorities of such city to carry such weapon.
Keywords: CARRY - CONCEALED